Lipolytic System of the Tomato Pathogen Fusarium oxysporum f. sp. lycopersici - Gustavo Bravo-Ruiz; Carmen Ruiz-Roldán; M. Isabel G. Roncero (Molecular Plant-Microbe Interactions, 2013)
The lipolytic profile of Fusarium oxysporum f. sp lycopersici was studied by in silico search and biochemical enzyme activity analyses. Twenty-five structural secreted lipases were predicted based on the conserved pentapeptide Gly-X-Ser-X-Gly-, characteristic of fungal lipases, and secretion signal sequences. Moreover, a predicted lipase regulatory gene was identified in addition to the previously characterized ctf1. The transcription profile of thirteen lipase genes during tomato plant colonization revealed that lip1, lip3, and lip22 were highly induced between 21 and 96 h after inoculation. Deletion mutants in five lipase genes (lip1, lip2, lip3, lip5, and lip22) and in the regulatory genes ctf1 and ctf2 as well as a Δctf1Δctf2 double mutant were generated. Quantitative reverse transcription-polymerase chain reaction expression analyses of structural lipase genes in the Δctf1, Δctf2, and Δctf1Δctf2 mutants indicated the existence of a complex lipase regulation network in F. oxysporum. The reduction of total lipase activity, as well as the severely reduced virulence of the Δctf1, Δctf2, and Δctf1Δctf2 mutants, provides evidence for an important role of the lipolytic system of this fungus in pathogenicity.